Gastropods of Taylor County, Texas - Clark W. Beasley; Richard W. Fullington (Hello World!, 1978)
Twenty-nine land and freshwater gastropod species are now recorded for Taylor County, Texas. This relatively small number is somewhat surprising for a Texas county that should potentially harbor a much larger molluscan fauna.